2021
DOI: 10.3390/metabo11090574
|View full text |Cite
|
Sign up to set email alerts
|

Impaired HMG-CoA Reductase Activity Caused by Genetic Variants or Statin Exposure: Impact on Human Adipose Tissue, β-Cells and Metabolome

Abstract: Inhibition of 3-hydroxy-3-methyl-glutaryl-CoA (HMG-CoA) reductase is associated with an increased risk of new-onset type 2 diabetes. We studied the association of genetic or pharmacological HMG-CoA reductase inhibition with plasma and adipose tissue (AT) metabolome and AT metabolic pathways. We also investigated the effects of statin-mediated pharmacological inhibition of HMG-CoA reductase on systemic insulin sensitivity by measuring the HOMA-IR index in subjects with or without statin therapy. The direct effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Increased LDL cholesterol uptake, which is responsible for lipid lowering effects, takes place predominantly in the liver (Hafner et al, 2011). However, increased cholesterol uptake was also observed in other organs and tissues (Sarsenbayeva et al, 2021). In this scenario, it was connected with abnormal organ function, leading to insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Increased LDL cholesterol uptake, which is responsible for lipid lowering effects, takes place predominantly in the liver (Hafner et al, 2011). However, increased cholesterol uptake was also observed in other organs and tissues (Sarsenbayeva et al, 2021). In this scenario, it was connected with abnormal organ function, leading to insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Our metabolomics study showed that genetic inhibition of HMG-CoA reductase was negatively correlated with sphingomyelins and phosphatidylcholines, which increase insulin resistance (15). Sarsenbayeva et al (84) investigated the association of genetic or pharmacological HMG-CoA reductase inhibition in adipose tissue and concluded that high concentrations of simvastatin decreased adipocyte glucose uptake. They also found a positive association of HMGCR with the insulin signalling pathway, suggesting that reduced activity of HMGCR may contribute to insulin resistance.…”
Section: Mechanisms Leading To Incident Diabetes With Statin Medicati...mentioning
confidence: 92%
“…Sarsenbayeva et al. ( 84 ) investigated the association of genetic or pharmacological HMG-CoA reductase inhibition in adipose tissue and concluded that high concentrations of simvastatin decreased adipocyte glucose uptake. They also found a positive association of HMGCR with the insulin signalling pathway, suggesting that reduced activity of HMGCR may contribute to insulin resistance.…”
Section: In Vitro and In Vivo Studies On ...mentioning
confidence: 99%
“…118 In the presence of macrophages, glucocorticoids may exert profibrotic effects and adipose tissue fibrosis. 119 It is possible to speculate that autophagy may be involved in this process because autophagy receptors regulate the macrophage functions. 120 Conversely, autophagy inhibition may prevent glucocorticoid-induced obesity.…”
Section: Immunosuppressive Drugs and Autophagymentioning
confidence: 99%